Recent measurements of the electric potential profile and fluctuations in ECRH and NBI plasmas on TJ-II stellarator - Krupnik, L.I.; Melnikov, A.V.; Hidalgo, C.; Eliseev, L.G.; Chmyga, A.A.; Komarov, A.D.; Kozachok, A.S.; Perfilov, S.V.; Lysenko, L.G.; Zhezhera, A.I.; Pedrosa, M.A.; de Pablos, J.L. (Вопросы атомной науки и техники, 2009)
Heavy Ion Beam Probe diagnostics is used in TJ-II stellarator to study directly the plasma electric potential with a good spatial (up to 1cm) and temporal (up to 2 µs ) resolution. Low density (ne = (0.3…0.5)×1019 m –3) ECRH plasma in TJ-II is characterized by positive plasma potential (ϕ(0) = +600…+ 400 V). At higher densities the minor area of the negative electric potential appears at the edge. This area increases with the density, finally makes potential fully negative. This tendency is affected by ECRH power and deposition area. The NBI plasmas are characterized by negative electric potential in the full plasma column from the center to the edge, (ϕ(0) = -300…-600 V). These results show the clear link between plasma potential, temperature, density and particle confinement.